Non-surgical management of ankle contracture following acquired brain injury. - Singer, B.; Dunne, J.; Singer, K.; Jegasothy, G.; Allison, Garry (Informa Healthcare, 2004)
BACKGROUND AND PURPOSE: The purpose of this study was to document the outcome of non-surgical management of equinovarus ankle contracture in a cohort of patients with acquired brain injury admitted to a specialist Neurosurgical Rehabilitation Unit. METHODS: This prospective descriptive study examined all patients with a new diagnosis of moderate to severe acquired brain injury (Glasgow Coma Scale score <12) admitted for rehabilitation over a 1 year period. Ankle dorsiflexion range and plantarflexor/invertor muscle activity were evaluated weekly during the period of hospitalization. Contracture was defined as maximal passive range of motion <0 degrees dorsiflexion, with the knee extended, on a minimum of two measurement occasions. Patients were retrospectively allocated to one of four treatment outcome categories according to ankle dorsiflexion range, type of intervention required and response to treatment. RESULTS: Ankle contracture was identified in 40 of the 105 patients studied. Contracture resolved with a standard physiotherapy treatment programme, including prolonged weight-bearing stretches and motor re-education, in 23 patients. Contracture persisted or worsened in 17 of 40 cases, all of whom exhibited dystonic muscle overactivity producing sustained equinovarus posturing. Ten of 17 cases required serial plaster casting (+/- injection of botulinum toxin type A) in order to achieve a functional range of ankle motion. Remediation of ankle contracture was not considered a priority in the remaining seven patients due to the severity of their overall disability.CONCLUSION: The incidence of ankle contracture identified in this population was considerably less than previously reported. Reduced dorsiflexion range was remediated with standard physiotherapy treatment in over half of the cases. Additional treatment with serial casting +/- botulinum toxin type-A injection was required to correct persistent or worsening contracture in one quarter of cases. Dystonic extensor muscle overactivity was a major contributor to persistent or progressive ankle contracture.